Developing AI and Machine Learning Models for Business Optimization - Martsenyuk, Vasyl; Gancarczyk, Tomasz; Kłos-Witkowska, Aleksandra (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
Artificial Intelligence (AI) enables machines to mimic human intelligence. It involves simulating cognitive functions such as learning, reasoning, problem-solving, perception, and language understanding. AI can be programmed to perform tasks that typically require human judgment, enabling automation in various domains. Machine Learning (ML) is a subset of AI that allows systems to learn from data and improve over time. Instead of being explicitly programmed for every task, ML algorithms identify patterns in historical data and apply these patterns to make predictions or decisions without human intervention. As more data becomes available, the model's accuracy and performance can improve. Businesses use AI/ML to increase efficiency, reduce costs, and make data-driven decisions. These technologies help streamline operations, eliminate repetitive tasks, enhance customer experiences, and provide insights that inform strategic choices. By leveraging AI/ML, companies can gain a competitive edge in fast-paced markets.